ANALISIS KESULITAN GURU DALAM MENGAJAR MATEMATIKA DI KELAS IV - Mutiah Dina Maya; Muhammad Rif’an; Shaqila Rizky D.A; Riani Tazkia Hadi; Elvi Mailani (Jurnal Keluarga Sehat Sejahtera, 2024)
This study aims to analyze the difficulties faced by teachers in teaching mathematics on multiplication and subtraction downwards in class IVB of SD Negeri 060877 Medan Perjuangan. This study uses a qualitative approach with a phenomenological method. Data were collected through observation, interviews, and documentation, with the principal and fourth-grade teachers as the main informants. The results showed that teachers experienced difficulties due to the heterogeneity of students' abilities, limited learning time, and a lack of available learning media. Students had difficulty understanding the concepts of multiplication and subtraction due to their weak foundation in mathematical operations, lack of understanding of place value, and anxiety towards mathematics. To overcome these difficulties, it is recommended to use concrete teaching aids, more varied learning strategies, and provide additional guidance for students who experience difficulties. It is hoped that these findings will serve as input for improving the quality of mathematics learning in elementary schools.